Influence of Employee Welfare Services on Employee Performance in Mumias Sugar Company, Kenya - Cherutich, Andrew Kipkemoi (JOOUST, 2018)
Employee welfare is a term that includes various services, benefits and facilities offered to employees by the employers. Welfare helps in keeping the morale and motivation of the employees high so as to retain the employees for longer duration. Employee welfare has been promoted and recommended as a means of improving performance in organizations, its effect on the performance of employees in the sugar sector has not been exhaustively investigated. The influence of employee welfare services on the performance of employees is therefore unknown in whole, yet Mumias Sugar Company has embraced employee welfare services as a core strategy. The study therefore sought to investigate the influence of employee welfare services on employee performance in Mumias Sugar Company. The specific objectives were to establish the influence of individual services, group services, counseling services and employee assistance on employee performance in Mumias Sugar Company. The research design adopted for this study was a Case study. The target population for this study was 260 employees of Mumias Sugar Company. The sample size was 155 employees of Mumias Sugar Company. The sample size was determined according to Krejcie and Morgan (1970) model of sample size. This study employed stratified and simple random sampling methods. Data was collected using Likert questionnaires and interviews. Validity was ensured through use of experts who are the supervisors of the researcher. Reliability was determined by test-re-test method. Data was analyzed through descriptive and multi¬regression techniques. The study was important to the management of Mumias in that the findings will enable them to know which welfare services to invest more in so as to guarantee increased employee performance. It can also be a source of secondary data for future researchers. The study found out that welfare services influences employee effectiveness (F-ratio=7.442;p<.05),welfare services influences employee efficiency,(F¬RATIO=15.446;p<.05) and employee welfare influences employee service delivery,(F¬ratio=10.544;p<.05). It was concluded that it was prudent for Mumias Sugar Company, through the HR office but in consultation with other departments to strengthen existing employee welfare programs and possibly invest in more• new programs. The study concludes that MSC should be at the forefront in initiating employee scheme programs as discussed so as not only to benefit their employees but to also enhance their performance as a company. The study recommends for further research to establish other factors of employee welfare that affect employee performance since the researcher was not able to cover all the factors.